Designed by law: Purpose, accountability, and transparency at benefit corporations - Dilek Cetindamar (Cogent Business & Management, 2018)
The article explores the realization of major goals of the Benefit Corporation (BC) law, which is a corporation form designed for social enterprises in the United States in 2010. BCs have a dual mission of generating both profit and social value and hence they might have the potential to transform society. This paper attempts to observe the first movers established as BCs during the period of 2010–2012. By adopting the institutional theory approach, the study examines the realization of the BC law's three major goals: purpose, accountability, and transparency. The paper utilizes the regulatory legitimacy concept to measure the discrepancy between design and implementation of law. The observations point out some of the challenges of establishing new innovative organizations through an institutional intervention of a law. Conclusions consist of implications of the study as well as suggestions for further studies.
Keywords: 650